pH-Sensitive Alginate/Carboxymethyl Chitosan/Aminated Chitosan Microcapsules for Efficient Encapsulation and Delivery of Diclofenac Sodium - Ahmed M. Omer; Maha S. Ahmed; Gehan M. El-Subruiti; Randa E. Khalifa; Abdelazeem S. Eltaweil (MDPI AG, 2021)
To develop an effective pH-sensitive drug carrier, alginate (Alg), carboxymethyl chitosan (CMCs), and aminated chitosan (AmCs) derivatives were employed in this study. A simple ionic gelation technique was employed to formulate Alg-CMCs@AmCs dual polyelectrolyte complexes (PECs) microcapsules as a pH-sensitive carrier for efficient encapsulation and release of diclofenac sodium (DS) drug. The developed microcapsules were characterized by Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analyzer (TGA), and scanning electron microscope (SEM). The results clarified that formation of dual PECs significantly protected Alg microcapsules from rapid disintegration at colon conditions (pH 7.4), and greatly reduced their porosity. In addition, the dual PECs microcapsules can effectively encapsulate 95.4% of DS-drug compared to 86.3 and 68.6% for Alg and Alg-CMCs microcapsules, respectively. Higher DS-release values were achieved in simulated colonic fluid [SCF; pH 7.4] compared to those obtained in simulated gastric fluid [SGF; pH 1.2]. Moreover, the drug burst release was prevented and a sustained DS-release was achieved as the AmCs concentration increased. The results confirmed also that the developed microcapsules were biodegradable in the presence of the lysozyme enzyme. These findings emphasize that the formulated pH-sensitive microcapsules could be applied for the delivery of diclofenac sodium.